THU0336 Giant cell arteritis (GCA) in octogenarian patients. (15th June 2017) - Solans-Laqué, R; Fonseca, E; Escalante, B; Martinez-Zapico, A; Fraile, G; Conesa, M; Abdilla, M; Monteagudo, M; Lasso, J; Calvo, E; Gracia, B; Castillo, M; et al.
Abstract : Background: GCA is the most common systemic vasculitis in elderly people. It is characterized by granulomatous involvement of the major branches of the aorta with predilection for the temporal arteries. Headache is the most frequent initial complaint, and permanent visual loss the most feared complication. Objectives: to describe the initial manifestations and outcome of CGA in octogenarian patients, and to investigate if there are some differences compared to younger patients Methods: demographic, clinical and histological features, treatment and outcome of all patients with biopsy-proven GCA recruited at 11 different Hospitals from Spain (REVAS Study) were analysed. Statistical analysis was performed using SPSS vs. 20 Results: among the 418 patients included in the study, 180 (27.5%) were older than 80 y at disease onset (mean age 83.77±3.1, range 80–92y). Cardiovascular risk factors (hypertension, hypercholesterolemia, diabetes) were more prevalent in octogenarian patients than in younger (73% vs. 50%, p=0.018). Headache was the most frequent initial complaint (78.5%), followed by polymyalgia rheumatica (49.6%), jaw claudication (48.7%) and toxic syndrome (43.5%). A total of 28 (24.35%) patients suffered permanent visual loss, due to anterior ischemic optic ischemic neuropathy (n=26) or central retina vein thrombosis (n=4). When compared with younger patients, neither headache, nor jaw claudication, nor scalp tenderness and polymyalgia, were more common in octogenarian patients. Only fever was less common in patients >80 y at diagnosis than in younger (27.7% vs. 72.3%, p=0.006), and permanent visual loss was most prevalent among octogenarian patients (24.3% vs. 15.7%, OR 1.73, 95CI 1.1–2.9, p=0.04). We found an inverse correlation between fever and permanent visual loss (p=0.001). Blindness was significantly correlated with jaw claudication (p=0.006) and amaurosis fugax (p=0.001). We did not found any significant correlation between blindness and vascular risk factors. Regarding to LAB, ESR was higher in octogenarian patients (p=0.006) as well as thrombocytosis >400.000 platelets/mm (p=0.026). No differences were found related to anaemia prevalence. Inflammatory infiltrate with lumen occlusion and giant cells were significantly more prevalent in temporal artery biopsies from patients with permanent bilateral visual loss (p=0.007 and p=0.01, respectively). No differences were found related to treatment. All patients received oral prednisone at tapering dosage, 85.9% calcium and vitamin D supplementation, and 60% bifosfonates. We did not found differences related to treatment-side effects (osteoporotic fracture, diabetes, infections) between octogenarian patients and the younger. Conclusions: octogenarian patients with GCA have an increased risk of developing permanent visual compared to younger patients. The presence of jaw claudication and amaurosis fugax must prompt to initiate corticosteroid treatment quickly. No differences were found related to treatment side effects in octogenarian patients. Disclosure of Interest: None declared